Effects of Delayed Finishing/Polishing on Surface Roughness, Hardness and Gloss of Tooth-Coloured Restorative Materials - Yazici, A Ruya; Tuncer, Duygu; Antonson, Sibel; Onen, Alev; Kilinc, Evren (European Journal of Dentistry, 2010)
Objectives: The aim of this study was to investigate the effect of delayed finishing/polishing on the surface roughness, hardness and gloss of tooth-coloured restorative materials.Methods: Four different tooth-coloured restoratives: a flowable resin composite- Tetric Flow, a hybrid resin composite- Venus, a nanohybrid resin composite- Grandio, and a polyacid modified resin composite- Dyract Extra were used. 30 specimens were made for each material and randomly assigned into three groups. The first group was finished/polished immediately and the second group was finished/polished after 24 hours. The remaining 10 specimens served as control. The surface roughness of each sample was recorded using a laser profilometer. Gloss measurements were performed using a small-area glossmeter. Vickers microhardness measurements were performed from three locations on each specimen surface under 100g load and 10s dwell time. Data for surface roughness and hardness were analyzed by Kruskal Wallis test and data for gloss were subjected to one-way ANOVA and Tukey test (P<.05).Results: The smoothest surfaces were obtained under Mylar strip for all materials. While there were no significant differences in surface roughness of immediate and delayed finished/polished Dyract Extra samples, immediately finished/polished Venus and Grandio samples showed significantly higher roughness than the delayed polished samples (P<.05). In Tetric Flow samples, immediately finishing/polishing provided smoother surface than delayed finishing/polishing (P<.05). The highest gloss values were recorded under Mylar strip for all materials. While delayed finishing/polishing resulted in a significantly higher gloss compared to immediate finishing/polishing in Venus samples (P<.05), no differences were observed between delayed or immediate finishing/polishing for the other materials (P>.05). The lowest hardness values were found under Mylar strip. Delayed finishing/polishing significantly increased the hardness of all materials.Conclusions: The effect of delayed finishing/polishing on surface roughness, gloss and hardness appears to be material dependent. (Eur J Dent 2010;4:50-56)
Keywords: Hardness; Roughness; Gloss; Tooth-coloured restorative materials; Finishing; Polishing